Scab Labor - Dan Bernhardt; John Spicer (Queen's University, Department of Economics, 1995)
This paper explores the political economy of unions, and the consequences this has for bargaining and strikes. We develop a very simple model to show that there are circumstances in which everyone, including striking workers, gains when some employees cross the picket line. We detail how strikes can emerge in equilibrium despite the absence of uncertainty, and how this strike outcome can Pareto dominate the outcome when scabbing is illegal, despite the fact that the strike destroys surplus. We also characterize when the firm might prefer to lock out those workers who would be strike breakers.
Keywords: J50; J51; 330; strikes; scabs; lock-outs